Lack of a synergistic effect of arginine-glutamic acid on the physical stability of spray-dried bovine serum albumin - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2017)
Improving the physical stability of spray-dried proteins is essential for enabling pulmonary delivery of biotherapeutics as a noninvasive alternative to injections. Recently, a novel combination of two amino acids - l-arginine (l-Arg) and l-glutamic acid (l-Glu), has been reported to have synergistic protein-stabilizing effects on various protein solutions. Using spray-dried bovine serum albumin (BSA) reconstituted in solution as a model protein, we investigated the synergistic effect of these amino acids on the physical stability of proteins. Five BSA solutions were prepared: (1) BSA with no amino acids (control); (2) with 50mM l-Arg; (3) with 200mM l-Arg, (4) with 50mM l-Glu and (5) with 25:25mM of Arg:Glu. All solutions were spray-dried and accelerated studies at high temperatures were performed. Following accelerated studies, monomer BSA loss was measured using SE-HPLC. We found that l-Arg significantly improved the physical stability of spray-dried BSA even at low concentrations, however, when combined with l-Glu, was ineffective at reducing monomer BSA loss. Our findings demonstrate the limitations in using Arg-Glu for the stabilization of spray-dried BSA. Furthermore, we found that a low concentration of l-Glu enhanced monomer BSA loss. These findings may have significant implications on the design of future biotherapeutic formulations.
Keywords: Amino acids; excipients; physical stability; protein aggregation; spray-drying; AMINO-ACIDS; PROTEIN SOLUBILITY; DELIVERY; STABILIZATION; AGGREGATION; CHALLENGES; STRATEGIES; MIXTURES